2002
DOI: 10.1097/00005537-200204000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Treatment Results for Oral Tongue Cancer

Abstract: Significant improvement in DSS was seen in patients with clear margins, early stage grouping and clinical (pretreatment) tumor stage, and negative nodes. Significant decrease in DSS was seen in patients with close or involved margins, advanced stage grouping and clinical (pretreatment) tumor staging, positive clinical (pretreatment) node staging, and tumor recurrence. Obtaining clear margins of resection is crucial because it significantly affects survival. A minimum of 5 years of close monitoring is recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(145 citation statements)
references
References 15 publications
14
126
2
3
Order By: Relevance
“…No randomised controlled trials have yet been performed to compare the effectiveness of surgery with chemoradiation, and the usefulness of chemoradiation therapy involving systemic chemotherapy thus remains to be clarified. After surgery, the 5-year survival rate ranged from 27 to 60% of stage III patients, while it ranged from approximately 12 to 40% of stage IV patients (Chen et al, 1999;Sessions et al, 2002;Greenberg et al, 2003;Lo et al, 2003;Gorsky et al, 2004;Liao et al, 2006;Fan et al, 2007); our results were therefore similar to the results after surgery. In particular, the results of arterial injection therapy by cisplatin with sodium thiosulphate were excellent.…”
Section: Discussionsupporting
confidence: 80%
“…No randomised controlled trials have yet been performed to compare the effectiveness of surgery with chemoradiation, and the usefulness of chemoradiation therapy involving systemic chemotherapy thus remains to be clarified. After surgery, the 5-year survival rate ranged from 27 to 60% of stage III patients, while it ranged from approximately 12 to 40% of stage IV patients (Chen et al, 1999;Sessions et al, 2002;Greenberg et al, 2003;Lo et al, 2003;Gorsky et al, 2004;Liao et al, 2006;Fan et al, 2007); our results were therefore similar to the results after surgery. In particular, the results of arterial injection therapy by cisplatin with sodium thiosulphate were excellent.…”
Section: Discussionsupporting
confidence: 80%
“…18 The presence of compromised margins, which was statistically significant (p=0.004) in our sample, agrees with Sessions et al's results in showing that compromised margins decreased disease-free survival; these authors also found that when patients with compromised margins underwent postoperative radiotherapy, disease-specific survival increased significantly. 8 Chao et al also demonstrated that postoperative radiotherapy provided good results in patients with compromised margins; this group of patients had the same survival and local control that was found in patients with free margins. Postoperative radiotherapy did not improve survival in our sample.…”
Section: Discussionmentioning
confidence: 69%
“…Mortality rates have ranged from 2.16 to 2.96 for each 100,000 males and 0.48 and 0.70 for each 100,000 females 6 between 1979 and 1998 in Brazil; the mortality rate has increased at an annual 0.72% rate.7 According to Sessions et al, the 5-year survival rate remains low, at about 48% (overall survival) and 57% (disease-specific survival). 8 The biological behavior of oral SCC is uncertain; many of these tumors have an aggressive biological behavior at initial stages with early regional metastases and death. On the other hand, advanced tumors may metastasize slowly, and these patients may remain disease-free for long periods after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki, and Wallwork, studied patients with T1/T2 floor of mouth SCC, however these studies are suboptimal as they included patients with clinically positive lymph nodes which possibly could skew significant cut-off values [8,9]. [10]. Offering adjuvant radiotherapy to all low-stage patients would expose a larger subpopulation to unnecessary, harmful toxicities.…”
Section: Predictors Of Occult Metastases: Tumor Depth Of Invasionmentioning
confidence: 99%